Development of learning media introduction to table tennis sports equipment based on augmented reality - Ilham, Al; Datau, Suriyadi; Ikhsan, Haerul (Universitas Riau, 2024)
(Indonesian)Penelitian ini bertujuan untuk mengetahui kelayakan aplikasi Jambura Table Tennis (JTT) yang merupakan produk pengembangan berbasis augmented reality pada pembelajaran tenis meja. Metode pengembangan menggunakan model Multimedia Development Life Cycle (MDLC). Adapun tahapan yang dilakukan: 1) Pengonsepan ide produk melalui wawancara dan observasi lapangan, 2) Perancangan produk yang akan dikembangkan, 3) pengumpulan bahan yang dibutuhkan, 4) Pembuatan produk, 5) Pengujian alpha dan beta oleh ahli media dan ahli isi yang menggunakan uji Gregory validasi 100% serta uji efektifitas perorangan 95,4%, uji kelompok kecil dengan subjek 7 orang 95,57% dan uji lapangan kelayakan produk dengan subjek 33 orang kelas X SMA N 1 Dulupi sebesar 89%, 6) Pendistribusian produk aplikasi Jambura Table Tennis (JTT). Dari hasil tersebut dapat disimpulkan bahwa produk aplikasi Jambura Table Tenis (JTT) sangat valid dan layak untuk digunakan di SMAN 1 Dulupi. Adapun kelebihan dari produk ini yaitu lebih flesibel karena dapat digunakan di smartphone masing-masing siswa serta tidak memerlukan data dalam penggunaannya, sedangkan kelemahan produk yaitu hanya membahas materi tentang pengenalan peralatan tenis meja (English)This study aims to determine the feasibility of the Jambura Table Tennis (JTT) application which is a product development based on augmented reality in table tennis learning. The development method uses the Multimedia Development Life Cycle (MDLC) model. The stages carried out are: 1) Conceptualizing product ideas through interviews and field observations, 2) Designing the product to be developed, 3) collecting the required materials, 4) Making the product, 5) Alpha and beta testing by media experts and content experts using the Gregory test with 100% validation and individual effectiveness test of 95.4%, small group test with 7 subjects 95.57% and field test of product feasibility with 33 subjects of class X SMA N 1 Dulupi of 89%, 6) Distribution of the Jambura Table Tennis (JTT) application product. From these results it can be concluded that the Jambura Table Tennis (JTT) application product is very valid and feasible for use at SMAN 1 Dulupi. The advantage of this product is that it is more flexible because it can be used on each student's smartphone and does not require data for use, while the weakness of the product is that it only discusses material about introducing table tennis equipment. Copyright © The Author (s) 2024Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.